2006
DOI: 10.1103/physrevlett.96.086102
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Ordered Structures of Cytosine and Cytidine5-Monophosphate Adsorbed at Au(110)/Liquid Interfaces

Abstract: It is demonstrated using reflection anisotropy spectroscopy that the adsorption of cytosine and cytidine -monophosphate at the Au(110) 1 x 2/electrolyte interface gives rise to ordered structures in which the base is oriented vertical to the surface and parallel to the [110] axis of the Au(110) plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
97
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(112 citation statements)
references
References 19 publications
15
97
0
Order By: Relevance
“…This might reflect conformational differences between wild-type and mutant proteins that affect the local environment around the FAD isoalloxazine ring [12]. As with the wild-type ETF, the ETF 1e /ETF 2e couple was ⪡ −250mV for the engineered ETF proteins and not accessible [9] using this method.RAS is a surface-sensitive optical technique that has been used to probe molecular assembly and changes in molecular orientation at metal/liquid interfaces [13][14][15][16][17]. The preparation of the Au(110) single crystal used to immobilize engineered variants of ETF together with a description of the electrochemical cell, potentiostat and RAS instrument [18] have been described previously [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This might reflect conformational differences between wild-type and mutant proteins that affect the local environment around the FAD isoalloxazine ring [12]. As with the wild-type ETF, the ETF 1e /ETF 2e couple was ⪡ −250mV for the engineered ETF proteins and not accessible [9] using this method.RAS is a surface-sensitive optical technique that has been used to probe molecular assembly and changes in molecular orientation at metal/liquid interfaces [13][14][15][16][17]. The preparation of the Au(110) single crystal used to immobilize engineered variants of ETF together with a description of the electrochemical cell, potentiostat and RAS instrument [18] have been described previously [15].…”
mentioning
confidence: 99%
“…The preparation of the Au(110) single crystal used to immobilize engineered variants of ETF together with a description of the electrochemical cell, potentiostat and RAS instrument [18] have been described previously [15]. Electrolyte solutions were prepared from 0.1 M NaH 2 PO 4 and K 2 HPO 4 dissolved in ultra-pure water.…”
mentioning
confidence: 99%
“…We identify it with the phase reported in STM studies in electrochemical cells 22,28 , and by optical studies in solution 26 . In the last study, the measurements were performed in situ, and the molecules were found to be perpendicular to the surface and oriented along [1 1 0], whereas we found an intermediate angle.…”
Section: Adsorption Modelmentioning
confidence: 60%
“…The adsorption of cytosine on gold has been the subject of numerous studies using a wide range of techniques, such as STM, theoretical calculations, infrared and surface enhanced Raman spectroscopy and cyclic voltammetry [18][19][20][21][22][23][24][25][26][27] . Adsorption has been carried out in vacuum, in solution and in electrochemical cells, and on single crystals, thin films and nanoparticles of gold.…”
Section: Introductionmentioning
confidence: 99%
“…This is one of relatively few anisotropic metal substrates that can be prepared under ambient conditions using the flame annealing technique developed and used successfully by electrochemists. An example of the potential of RAS in exploring this electrochemical interface is a study of the adsorption of the DNA base cytosine and cytidine 5 -monophosphate from solutions of NaH 2 PO 4 and K 2 HPO 4 [58]. Ordered structures were formed on the Au surface, and analysis of the RAS results showed that the plane of the nucleic acid base was oriented vertically and was parallel to the [110] axis of the Au(110) surface.…”
Section: Solid-liquid Interfacesmentioning
confidence: 99%